Working with coaches and their teams in youth and collegiate sport in the USA: An interview with Dr Andy Gillham - Leading article - Jenkins, S. P. R. (International Journal of Sports Science & Coaching, 2018)
Insights are provided from a coaching consultant`s work with sports teams, including helping coaches in figure skating cope with parents who were always in their way; being unable to help a women`s soccer coach eliminate toxic behaviour from senior players; devising a goal setting programme involving peer assessment in women`s soccer that was successful in motivating reserve players on the bench during matches; empowering a pitcher in women`s softball as a solution to a head coach`s poor relationship with his pitching coach; facilitating culture change in a figure skating club by rewriting the club coaching contracts; and improving team cohesion in women`s volleyball through role play in the locker room.